Pests of tulsi (ocimum tenuiflorum L ) and their management - Malini Nilamudeen (Department of Agricultural Entomology, College of Agriculture, 2007)
The seasonal occurrence and the extent of damage caused by pests of tulsi were assessed in a survey conducted at monthly intervals for one year in five locations viz., Perumpazhuthoor, Parasuvaikkal, Poojapura, Peroorkada and Vellayani of Thiruvananthapuram district. A field trial was carried out in the Instructional Farm, College of Agriculture, Vellayani to evaluate the effect of various botanicals against the pests, the spiders and on herbage yield of tulsi.